Development of an MFL Coil Sensor for Testing Pipes in Extreme Temperature Conditions - Nagu Sathappan; Mohammad Osman Tokhi; Liam Penaluna; Zhangfang Zhao; Fang Duan; Gholamhossein Shirkoohi; Aman Kaur (Sensors, 2021)
This paper aims to design a coil sensor for corrosion monitoring of industrial pipes that could detect variations in thickness using the MFL (Magnetic Flux Leakage) technique. An MFL coil sensor is designed and tested with pipe sample thicknesses of 2, 4, 6, and 8 mm based on the magnetic field effect of ferrite cores. Moreover, a measurement setup for analysing pipe samples up to a temperature of 200° Celsius is suggested. Experimental results reveal that the MFL coil sensor can fulfil the requirements for MFL testing of pipes in high temperature conditions, and that the precision of MFL monitoring of pipes to detect corrosion at high temperatures can be improved significantly.